Morphofunctional pecularrities and sialoglicans in lungs from offspring born from female rats with thyroid gland hyperfunction - Kh. I. Strus; L. V. Pankevych; I. V. Chelpanova; O. V. Yuzich; A. M. Yashchenko; A. D. Lutsyk (Морфологія, 2020)
Background. Over the last decade, there has been a global pending to increase the incidence of chronic obstructive pulmonary disease by 25% in men and 69% in women. Objective. To study the role of sialoglycans according to wheat germ lectin receptors (WGA) and morphofunctional features of offspring rats, which developed in conditions of hyperfunction of the thyroid gland of the maternal organism. Methods. The experimental study was performed on the offsprings of 20 females (10 control, 10 experimental) rats of the Wistar line. For 20 days before coupling the females of the experimental group received the drug L-thyroxine (Berlin-Chemie) at a dose of 150 μg / kg body weight. After euthanasia by overdose of ether anesthesia, the offspring from control and experimental females were taken lungs on the 1st, 10th, 20th and 40th day of postnatal development. Histological material was fixed in 4% neutral formalin, compacted and poured into paraffin blocks, made sections 5-7 μm thick. Review preparations were stained with hematoxylin and eosin according to standard methods. Wheat germ lectin WGA (Triticum vulgare) labeled with peroxidase-specific DGlcNAc NeuNAc was used to detect sialoglycans. Results. On the 1-40th day of postnatal development, the lungs of rats of the intact group show up typical morphology characteristic of rat lungs. On the tenth day of postnatal development in the offsprings lungs from females receiving L-thyroxine visually increases the number of alveoli, indicating an intensification of morphogenesis of lung tissue. Lectinohistochemical studies showed that on the first day of postnatal development in the lungs of rats of the intact group, receptors for sialospecific lectin WGA were identified on the surface of ciliated cells of the bronchial tree and vascular endothelium, while in the experimental group receptors for this lectin were found significantly in alveolar macrophages, visualised more often than in the lungs of the offspring from rats of the control group. Whereas on the 20th-40th day of postnatal development the number of macrophages with the presence of sialoglycans decreased. Conclusion. Studies have shown that in the lungs of offsprings from females receiving L-thyroxine, there are processes of intensification of the structural components of the lungs and the appearance of alveolar macrophages with the presence of sialospecific lectin WGA receptors, the number of which decreases during postnatal ontogenesi, that indicating a decrease of the immunity.